A Study of Experiential Quality, Equity, Happiness, Rural Image, Experiential Satisfaction, and Behavioral Intentions for the Rural Tourism Industry in China. Issue 4 (2nd October 2017) - Wu, Hung-Che; Cheng, Ching-Chan; Ai, Chi-Han
ABSTRACT: This study aims at examining the interrelationships among experiential quality, equity, happiness, rural image, experiential satisfaction, and behavioral intentions for the rural tourism industry in China. The data used in this study were based on a sample of 694 rural tourists staying in Sansheng Flower Town of Chengdu, indicating that the proposed model fits the data. The result of this study will assist rural tourism management in developing and implementing market-orientated service strategies to increase experiential quality and equity, and enhance the image and experiential satisfaction of rural tourists in order to generate favorable intentions to return or revisit the same rural village.